The multiple intelligences application possibilities the French way - Nyerges , Katalin (Autonomy and Responsibility Journal of Educational Sciences, 2022)
A Guide pour enseigner autrement selon la théorie des intelligences multiples d'Howard Gardner (A guide to teaching differently based on Howard Garder's theory of multiple intelligences) published in 2009 by the Paris-based publisher Retz, with 11 authors and edited by Bruno Hourst...